Electrochemical evidence for inclusion complexes of thiotriazinone with cyclodextrins. Issue 86 (31st August 2016) - Arvinte, Adina; Marangoci, Narcisa; Nicolescu, Alina; Pinteala, Mariana
Abstract : Electrochemical behavior changes due to the formation of inclusion complexes. Abstract : The formation of the inclusion complexes of thiotriazinone (TTZ) with α-cyclodextrin and β-cyclodextrin was studied by cyclic voltammetry and 1 H-NMR. The oxidation and reduction reactions specific to thiotriazinone compounds are irreversible, diffusion controlled processes, and occur in a complex mechanism. The stable inclusion of thiotriazinone in β-cyclodextrin is proved by the significant changes of redox activity characteristic for TTZ and good electrochemical stability of the complex. Moreover, the present study demonstrates that β-cyclodextrin can serve as a carrier system, since the TTZ molecule can be gradually released from the inclusion complex with time.